Floating in situ gelling system for stomach site-specific delivery of clarithromycin to eradicate H. pylori - Rajinikanth P.S.; Mishra B. (My University, 2025)
Floating in situ gelling system of clarithromycin (FIGC) was prepared using gellan as gelling polymer and calcium carbonate as floating agent for potentially treating gastric ulcers, associated with Helicobacter pylori. Gellan based FIGC was prepared by dissolving varying concentrations of gellan in deionized water to which varying concentrations of drug and sucralfate were dispersed well. The formulation parameters like concentrations of gellan gum and sucralfate influenced the rate and extent of in vitro drug release significantly from FIGC. The addition of sucralfate to the formulation significantly suppressed the degradation of clarithromycin at low pH. The in vivo H. pylori clearance efficacy of prepared FIGC and clarithromycin suspension following oral administration, to H. pylori infected Mongolian gerbils was examined by polymerase chain reaction (PCR) technique and by a microbial culture method. FIGC showed a significant anti-H. pylori effect than that of clarithromycin suspension. The in situ gel formulation with sucralfate cleared H. pylori more effectively than that of formulation without sucralfate. In addition, the required amount of clarithromycin for eradication of H. pylori was found to be less from FIGC than from the corresponding clarithromycin suspension. It was concluded that prolonged gastrointestinal residence time and enhanced clarithromycin stability resulting from the floating in situ gel of clarithromycin might contribute better for complete clearance of H. pylori. © 2007 Elsevier B.V. All rights reserved.